2005
DOI: 10.1002/mnfr.200400059
|View full text |Cite
|
Sign up to set email alerts
|

Purification and determination of inhibitory activity of recombinant soyacystatin for surimi application

Abstract: A recombinant soyacystatin (r-soyacystatin) was tested for its inhibitory activity against cysteine proteinase of Pacific whiting and its activity was compared to that of egg white cystatin. A recombinant soyacystatin expressed in Escherichia coli was purified to electrophoretic homogeneity using phenyl-Sepharose and DEAE-Sepharose. Native egg white cystatin was purified by using affinity chromatography on CM-papain-Sepharose generated in our lab. Egg white cystatin and soyacystatin were tested for proteinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…18 The 18 kDa stefin purified from glassfish (Liparis tanakai) eggs inhibits cathepsins B/L more effectively than egg white cystatin (family II), and the results indicated that this glassfish stefin may be more suitable in preventing the deterioration of the surimi-gelling process. 19 Akpinar and An (2005) reported that recombinant cystatin from soya inhibits cathepsin L activity and the autolytic activity of Pacific whiting (Merluccius productus) surimi. 20 More robust evidence has been presented in our previous work: the gel-breaking force and gel strength of silver carp surimi are significantly enhanced The aforementioned studies have provided basic information for the application of piscine cystatins in fish muscle, fish fillets, and byproduct processing after clarifying their properties and distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The 18 kDa stefin purified from glassfish (Liparis tanakai) eggs inhibits cathepsins B/L more effectively than egg white cystatin (family II), and the results indicated that this glassfish stefin may be more suitable in preventing the deterioration of the surimi-gelling process. 19 Akpinar and An (2005) reported that recombinant cystatin from soya inhibits cathepsin L activity and the autolytic activity of Pacific whiting (Merluccius productus) surimi. 20 More robust evidence has been presented in our previous work: the gel-breaking force and gel strength of silver carp surimi are significantly enhanced The aforementioned studies have provided basic information for the application of piscine cystatins in fish muscle, fish fillets, and byproduct processing after clarifying their properties and distribution.…”
Section: Introductionmentioning
confidence: 99%
“…19 Akpinar and An (2005) reported that recombinant cystatin from soya inhibits cathepsin L activity and the autolytic activity of Pacific whiting (Merluccius productus) surimi. 20 More robust evidence has been presented in our previous work: the gel-breaking force and gel strength of silver carp surimi are significantly enhanced The aforementioned studies have provided basic information for the application of piscine cystatins in fish muscle, fish fillets, and byproduct processing after clarifying their properties and distribution. However, at this point, only fish-origin cystatins (family II) of chum salmon (Oncorhynchus keta), 21 common carp, 22,23 rainbow trout (Oncorhynchus mykiss), 24 Chinese sturgeon, 12 olive flounder (Paralichthys olivaceus), 4 and large yellow croaker 11 have been cloned or expressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of blood plasma renders the surimi product off-color and severely impairs the flavor. To solve this problem, microbially expressed protein additives (such as chicken and pineapple cystatin) are used to prevent the autolysis of mackerel surimi and Japanese tope shark (Hemitriakis japanica) surimi [24,25].…”
Section: Introductionmentioning
confidence: 99%